A Polymer‐Assisted Spinodal Decomposition Strategy toward Interconnected Porous Sodium Super Ionic Conductor‐Structured Polyanion‐Type Materials and Their Application as a High‐Power Sodium‐Ion Battery Cathode. Issue 11 (20th March 2021) - Xiong, Hailong; Qian, Ruicheng; Liu, Zhilin; Zhang, Rui; Sun, Ge; Guo, Bingkun; Du, Fei; Song, Shuyan; Qiao, Zhen‐An; Dai, Sheng
Abstract: A general polymer‐assisted spinodal decomposition strategy is used to prepare hierarchically porous sodium super ionic conductor (NASICON)‐structured polyanion‐type materials (e.g., Na3 V2 (PO4 )3, Li3 V2 (PO4 )3, K3 V2 (PO4 )3, Na4 MnV(PO4 )3, and Na2 TiV(PO4 )3 ) in a tetrahydrofuran/ethanol/H2 O synthesis system. Depending on the boiling point of solvents, the selective evaporation of the solvents induces both macrophase separation via spinodal decomposition and mesophase separation via self‐assembly of inorganic precursors and amphiphilic block copolymers, leading to the formation of hierarchically porous structures. The resulting hierarchically porous Na3 V2 (PO4 )3 possessing large specific surface area (≈77 m 2 g −1 ) and pore volume (≈0.272 cm 3 g −1 ) shows a high specific capacity of 117.6 mAh g −1 at 0.1 C achieving the theoretical value and a long cycling life with 77% capacity retention over 1000 cycles at 5 C. This method presented here can open a facile avenue to synthesize other hierarchically porous polyanion‐type materials. Abstract : A general polymer‐assisted spinodal decomposition strategy allows the synthesis of hierarchically porous carbon‐coated sodium super ionic conductor (NASICON)‐structured materials based on multiscale phase separation in both the mesoscopic and macroscopic ranges. The hierarchically porous Na3 V2 (PO4 )3 cathode exhibits an excellent activity for sodium‐ion batteries due to the combination of the advantages of the porous framework and inherent NASICON structure of NVP.